Controlling the impact dynamic behavior of a water-in-oil compound drop using the dielectrowetting effect. (5th June 2023) - Zheng, Jiangen; Mao, Mengge; Liu, Nanxi; Zuo, Ping; Yu, Ting; Fang, Ranran; Vorobyev, Anatoliy; Chen, Guo
Graphical abstract: Highlights: The dielectrowetting effect can control the impact behavior of a water-in-oil drop. Surface wettability of the dielectrowetting substrate is reversible and controllable. The maximum spreading factor presents two scale laws with Weber number. Threshold value of the maximum aspect ratio is independent of surface wettability. Abstract: Controlling the impact dynamic behavior of a water-in-oil compound drop is vital for applications such as the enhancement of printing resolution and the preparation of innovative liquid-separation materials and devices. A phase diagram is constructed between the impact behavior, Weber number, and equilibrium contact angle of the water drop. The dynamic impact behavior of water-in-oil compound drops can be effectively controlled by changing the surface wettability using the dielectrowetting effect. The maximum spreading factor β m at different wettabilities shares a similar scale law β m ∝ W e 0.17 for 45.75 < We < 299.62 and β m ∝ W e 0.23 for 385.38 < We < 1183.19. Finally, the relationship between the velocity and radius of the rebounded drops was consistent with the results for pure water drops. Our findings indicate that the impact behavior of water-in-oil compound drops can be controlled at the right time scales using a dielectrowetting substrate; this is applicable in industries such as printing and liquid separation.